Wearable wireless sensor network for human limbs monitoring - Tang, Wei Guang (2016)
This paper presents a novel idea to monitor human limb movement using a wearable wireless sensor network. The system configuration comprises of a mobile node, four anchors, one coordinator, one data transmission module and PC for signal processing. Modelling after the trilateration technique, the sensor network utilizes an ultrasonic transmitter to send out ultrasound signals to the four ultrasonic receivers on a planar plane to compute the positioning information between them. A highly sensitive pre-filter and Extended Kalman Filter are employed to determine the location of the mobile node along with the displacement information in the 3D Cartesian coordinate system. This proposed method of measurement can be a viable alternative to the current optical tracking system as it is cost-effective with low complexity involved. It harnesses the potential for longer monitoring duration to obtain accurate displacement information of the mobile node and can be useful for clinical assessment. Moreover, the positioning information can be extracted and combined with various modelling techniques like the inverse kinematic model for further analysis.